Semi Presidensil:Paradoks sistem pemerintahan di Indonesia - Yulion Zalpa (Fakultas Adab dan Humaniora UIN Raden Fatah, 2019)
Abstract This paper aims to parse and explain the dynamics of the political system and governance in Indonesia from the old order to reform. Post independence, Indonesia continues to look for a form of government system in order to realize democratic governance . Indonesia as a country has carried out “dismantling” the government system, such as presidential, parliamentary and even implementing a “semi-presidential” system. The current presidential system followed by the adoption of a multiparty system seems paradoxical, causing a lot of chaos and creating new problems in policy governance in Indonesia. The semi-presidential system affiliated with a multiparty system weakens the institutional and authority of the president as the leader of executive power. A multiparty system makes the president not independent in asserting political decisions. Furthermore, the multiparty system in parliament is filled with various political interests that open up wide space to interrupt presidential decisions and policies. This multiparty presence also further extended the decision making mechanism Keywords : semi-presidential, multiparty, political and government systems